Sistema de remuneração dos hospitais privados no Brasil: problemas e propostas de soluções - Manso Júnior, Glauco Monteiro Cavalcanti (2017)
The thesis deals with the remuneration system of private hospitals in Brazil, a sector that represents a considerable part of the offer of health services in Brazil, materializing the citizen's access to his right to health. The sector has suffered financial losses and has been accumulating losses due to the remuneration policies of both the SUS managers and the operators, threatening the viability of the enterprise and, consequently, the citizen service. The research aimed to identify measures to solve the problems caused by the hospital remuneration system (risks of destruction of hospitals, especially minors, increase of tension between operators and service providers) that indirectly harm the citizen. The methodology consisted of documentary analysis and research on foreign experiences in the constitution and management of hospital compensation systems. The first part of the paper deals with the health system and the hospital organization framework in the respective system. The second one approaches the hospital remuneration system, comparing the practices and systems adopted in France, Japan, Spain, United Kingdom, United States, Australia and Canada. The third analyzes the remuneration of the private hospital sector in Brazil, whose constitution includes the relationship with the SUS, the operators and the National Supplementary Health Agency (ANS). The fourth part presents the sector's remuneration prospects and presents the author's proposal. As a result, the research showed that the actions required to solve the problem are related to the federal government (revision of the price list paid to providers, simplification of the legal and regulatory apparatus and greater control over ANS decisions) and hospital organizations regarding the adoption of Strategies and practices aimed at the effectiveness and transparency of management